Bisphenol A and Risk Management Ethics. (29th January 2014) - Resnik, David B.; Elliott, Kevin C.
Abstract It is widely recognized that endocrine disrupting compounds, such as Bisphenol A, pose challenges for traditional paradigms in toxicology, insofar as these substances appear to have a wider range of low‐dose effects than previously recognized. These compounds also pose challenges for ethics and policymaking. When a chemical does not have significant low‐dose effects, regulators can allow it to be introduced into commerce or the environment, provided that procedures and rules are in place to keep exposures below an acceptable level. This option allows society to maximize the benefits from the use of the chemical while minimizing risks to human health or the environment, and it represents a compromise between competing values. When it is not possible to establish acceptable exposure levels for chemicals that pose significant health or environmental risks, the most reasonable options for risk management may be to enact either partial or complete bans on their use. These options create greater moral conflict than other risk management strategies, leaving policymakers difficult choices between competing values.